2022
DOI: 10.3389/fgene.2022.924877
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq analyses show that long non-coding RNAs are conspicuously expressed in Schistosoma mansoni gamete and tegument progenitor cell populations

Abstract: Schistosoma mansoni is a flatworm that causes schistosomiasis, a neglected tropical disease that affects over 200 million people worldwide. New therapeutic targets are needed with only one drug available for treatment and no vaccine. Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides with low or no protein-coding potential. In other organisms, they have been shown as involved with reproduction, stem cell maintenance and drug resistance, and they tend to exhibit tissue-specific expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Results for ( A ) SmLINC101519, ( B ) SmLINC110998, and ( C ) SmLINC175062. For comparison purposes, single-cell RNA-Seq data from Morales-Vicente et al, 2022 [ 28 ] was retrieved from ( http://verjolab.usp.br:8081/ ). LincRNA expression patterns across the single-cell clusters are shown with UMAP plots, colored by gene expression levels (blue = low, red = high), and the scale represents log10(UMIs+1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results for ( A ) SmLINC101519, ( B ) SmLINC110998, and ( C ) SmLINC175062. For comparison purposes, single-cell RNA-Seq data from Morales-Vicente et al, 2022 [ 28 ] was retrieved from ( http://verjolab.usp.br:8081/ ). LincRNA expression patterns across the single-cell clusters are shown with UMAP plots, colored by gene expression levels (blue = low, red = high), and the scale represents log10(UMIs+1).…”
Section: Resultsmentioning
confidence: 99%
“…SmLINC101519 was expressed in the female uterus, vitellaria and around the female ovary, while in males, SmLINC101519 was present in testes, oesophagus and along the head and trunk ( Fig 8A , right). Single-cell RNA-Seq (scRNA-Seq) analysis of lincRNAs expression [ 28 ] showed that SmLINC101519 was detected in parenchyma, muscle and neuron cell clusters ( Fig 8A , left, cells clusters marked with 1, 2 and 3) . Combining the WISH localization (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, lncRNAs have been identified in different developmental stages of S. mansoni, suggesting their involvement in stage-specific gene expression and potential as biomarkers (Rocha et al, 2022). Furthermore, the expression patterns of lncRNAs in S. mansoni have been characterized at the singlecell level, revealing tissue-specific expression and regulated expression programs (Morales-Vicente et al, 2022). In Schistosoma japonicum infection, lncRNAs have been implicated in the formation of liver granulomas and the polarization of macrophages, providing a potential target for treatment (Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%